PERAN STRATEGIS ADMINISTRASI PENDIDIKAN DALAM MENINGKATKAN AKSES PENDIDIKAN SISWA KURANG MAMPU DI SMKN 3 BANJARMASIN - Raisyah, Siti; Heru Arna Fama, Putri Medina; Setiyani, Tri Ananda; Aslamiah, Aslamiah; Cinantya, Celia (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2025)
This study aims to examine the strategic role of educational administration in improving access to education for students from low-income backgrounds at SMKN 3 Banjarmasin. This study uses a qualitative descriptive approach, data were collected through in-depth interviews, direct observation, and documentation studies. The results of the study indicate that educational administration plays a major role in designing and implementing educational assistance policies, such as scholarships, payment flexibility, and the ' Saudara Asuh' program. This program has proven effective in reducing students' economic burden and increasing their participation and enthusiasm for learning. This study also emphasizes the importance of empathy-based and participatory policies in inclusive education management.   Keywords: educational administration, access to education, education policy, economics, inclusive schools